AGE AND GENDER PECULIARITIES OF DEVELOPMENT OF GALLSTONE DISEASE - N. A. Hohlacheva; N. N. Sergeeva; Ya. M. Vahrushev (SINAPS LLC, 2016)
Goal. Study of the role of risk factors in mechanized gall stone formation depending on sex and age of patients. Material and methods We examined 210 patients with stage I gallstone disease (GSD). In verification of diagnosis used an ultrasound study of the hepatobiliary system, multi-grade duodenal sounding with subsequent macroscopic, microscopic, chemical and physical examination of bile. In the portions "b" and "C" bile was determined the total concentration of bile acids, cholesterol, with the subsequent calculation it consists of cholesterol ratio. Estimation of surface tension of bile viscosity and bile. In the studied blood levels of total cholesterol, lipoproteins of very low density, lowdensity lipoproteins, high density lipoproteins, triglycerides, were determined the coefficient of atherogenicity. To assess the degree of accumulation of body fat was used the Quetelet index. Studied the relative risk of anamnestic risk factors of GSD. Results. The features of biliary lithogenesis based on gender and age of patients. High value PR for the gall stone formation are female gender - 3,16, Mature and elderly age (older than 50) of 3.67. In young women, gall-stone formation is mainly due to the increase of cholesterol level of bile, at the age of 50 years with a decline in zhelchnokamennaja pool, increased viscosity and surface tension of bile. The most important risk factors of cholecystolithiasis are also gender differences: if women is multiple pregnancies and (or) childbirth (more than 3) - OR 4,62, overweight (BMI over 26) - OR is 4.57 and the violation of the principles of good nutrition (eating disorders, overeating or starvation, the use of large quantities of animal fats) - OR 3,94, for men it's physical inactivity - OR a 4.25, the increase in KA - PR 3.87 and burdened by GSD genetics - OR of 2.05. Conclusion. The data obtained can be used in the organization of dispensary work with patients with hepatobiliary pathology, and to optimize primary prevention of gall stone formation.